2020
DOI: 10.1002/cphc.202000133
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Solvated Electrons with Nucleobases: The Effect of Base Pairing

Abstract: We have investigated the effect of base pairing on the electron attachment to nucleobases in bulk water, taking the guanineÀ cytosine (GC) base pair as a test case. The presence of the complementary base reinforces the stabilization effect provided by water and preferentially stabilizes the anion by hydrogen bonding. The electron attachment in bulk-solvated GC happens through a doorway mechanism, where the initial electron attached state is water bound, and it subsequently gets converted to a GC bound state. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…The calculated rate is 5-fold larger from that observed for microsolvated states which highlight the crucial role played by the bulk water in electron attachment process. The rate of electron transfer from the initial water localized state to the final nucleobase localized state in bulk solvated cytosine is almost half of that observed for cytosine in bulk solvated GC base pair 57 . This indicates the cooperativity effect of base-pairing with the solvation in the electron attachment process.…”
Section: Mechanism Of Electron Attachment In Bulk Watermentioning
confidence: 77%
See 1 more Smart Citation
“…The calculated rate is 5-fold larger from that observed for microsolvated states which highlight the crucial role played by the bulk water in electron attachment process. The rate of electron transfer from the initial water localized state to the final nucleobase localized state in bulk solvated cytosine is almost half of that observed for cytosine in bulk solvated GC base pair 57 . This indicates the cooperativity effect of base-pairing with the solvation in the electron attachment process.…”
Section: Mechanism Of Electron Attachment In Bulk Watermentioning
confidence: 77%
“…The rates are much slower than those observed for microhydrated uracil 57 or microhydrated GC base pair. 58 However, microsolvation leads to at least a four-fold increase in the rate of transition from the gas-phase value of 1.6 × 10 5 s −1 . It shows that the presence of even one water molecule can increase the stability of the valence-bound state and consequently increases the rate of transfer of an electron from the dipole-bound to the valence-bound state, which is consistent with previously reported results.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Earlier work of Sommerfeld and our previous works , have shown the dipole-bound states as an efficient doorway for the capture of electrons in DNA bases. The picture becomes more complex in the presence of an aqueous solvent.…”
mentioning
confidence: 67%
“…We have recently shown that the doorway mechanism is a generalized path to the formation of stable nucleobase anion, 34 and this even exists in the condensed phase, where solvent-bound states act as a doorway state. [35][36][37] This raises the possibility of a doorway mechanism for LEE-induced DEA process in genetic materials. Previous studies have shown that purine nucleobases have the highest VEA among the nucleobases.…”
mentioning
confidence: 99%
See 1 more Smart Citation